PERAN GURU BIMBINGAN DAN KONSELING SERTA PERAN GURU MATA PELAJARAN DALAM MENGATASI KESULITAN BELAJAR SISWA DI SEKOLAH MENENGAH ATAS (SMA) NEGERI - Sudirman, Sudirman; Daharnis, Daharnis; Marjohan, Marjohan (Konselor, 2013)
This research was started from the presence of some students that had difficulties in learning and had learning outcomes under minimum criteria and there was symptoms  that teacher’s guidance counselling and subject teacher had less contribution to help students overcome in learning difficulties. The type of this research was descriptive. The population of this research were all the guidance and councelling teacher and subject teacher at SMAN Se-Kota Pekanbaru, they were 47 guidance and councelling teacher and 979 subject teacher. Data analysis was by using percentage technique and respondent performance level. The results of research showed that: 1) The role of teacher’s guidance counselling in overcoming difficulties student learning in high school in Pekanbaru city is included the category quite well, 2) The role of teacher’s lessons in overcoming difficulties student learning in high school in Pekanbaru city is included the category quite well and 3) The collaboration of  teacher’s guidance counselling with teacher’s lessons is included the category quite well, while the collaboration of teacher’s lessons with teacher’s guidance counseling in overcoming difficulties student learning in high school in Pekanbaru city is included the category quite well. Keyword: Peran, Guru Bimbingan Konseling, Guru Mata Pelajaran, Kesulitan Belajar